TURBIN ANGIN SAVONIUS EMPAT SUDU DENGAN VARIASI MODEL PROFIL SEBAGAI MEDIA BELAJAR MAHASISWA - Eka Sari Wijianti; Saparin Saparin; Yudi Setiawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2019)
This research is about making a prototype of four blades savonius wind turbine as a learning media for Energy Conversion in the Mechanical Engineering Department, Bangka Belitung University. The making of this learning media is due to the limitations of student practicum facilities to support the continuity of practical and conducive lectures. The prototype was made with small dimensions, namely a frame of 0.75m x 1.5m and a turbine blade diameter of 0.15x0.3m. A fan-assisted the study as a wind energy generator. Wind speed variations carried out at three rates following the wind speed generated by the fan. The rate of wind speed measured using an anemometer and the rotation using a tachometer. The current and voltage are measured using a multitester. Turbine blades are varied with 4 blades with three-blade profile models, namely U, L, and S. Research, shows that wind speed influences turbine performance. The higher the wind speed, the higher the rotor's rotation, and so the resulting power. The best profile is obtained from the L model, which reaches 177.63 rpm with 6.35 watts of power.